Diversity analysis of agronomic and nutritional traits of hybrid offspring of forage bermudagrass - Chen, Jianmin; Fan, Shugao; Li, Shuang; Cui, Xinyu; Amombo, Erick; Ji, Mingxia; Liu, Xiaoyan; Fu, Jinmin (Frontiers in Plant Science, 2023)
Because of its excellent stress resistance and forage quality, the forage bermudagrass hybrid population had attracted the attention of scientific researchers in recent years. Studying its diversity could promote the breeding of desirable varieties. The variability in agronomic traits including fresh weight, dry weight, ash content, crude protein content, crude fat, phosphorus content, and relative feed value for 56 bermudagrass was investigated using Wrangler as an experimental reference. Grey correlation analysis and cluster analysis were employed to screen bermudagrass with high yield and superior quality. WCF-34 had the highest 2-year fresh weight (109,773.3 kg/ha), WCF-37 had the highest 2-year dry weight (31,951.6 kg/ha), WCF-24 had the lowest Ash content (7.46%), WCF-26 had the highest crude protein content (16.27%), WCF-27 had the highest curde fat content (3.58%), WCF-13 had the highest P content (0.45%), and WCF-42 had the highest relative feed value (95.32). Combining the results of grey relational analysis and cluster analysis, WCF-42, WCF-34, WCF-38, WCF-37, and WCF-40 were selected as high-quality bermudagrass. Through comprehensive analysis of the agronomic characters of bermudagrass, five bermudagrass were selected, the outcomes of this study would provide a theoretical basis for the breeding and genetic enhancement of bermudagrass.